(untitled) (LACCEI, 2024)
Air pollution is a problem in several mining and metallurgical operations, which can increase if the processing plants do not respect environmental standards. This work evaluates air quality with three monitoring stations in the years 1999, 2008 and 2014 in the city of La Oroya, near the Metallurgical Complex of the same name. The method used in this research was the grey clustering method, which is based on the grey systems theory. This technique allows working with data with a high degree of incertitude. An example would be the air quality analysis data. The results of this investigation reveal that in the year 1999 the air quality was extremely poor, while in 2008 it varied from poor to extremely poor however, in 2014 the calculations show that the quality is good. These conclusions are obtained from the Ontario Ambient Quality Criteria (AAQC) and the Metropolitan Air Quality Index (IMECA). The results of this inquiry could motivate the competent authorities to carry out more studies to confirm that the air quality in La Oroya is good, since it was ranked as the fifth most polluted city.